Comparative Analysis of the Quality of Pandan Glutinous Rice Talam Cake and Talam Cake With Dragon Fruit Peel Extract (Hylocereus Polyrhizus) - Fitri Wulandari; Anni Faridah; Kasmita; Cici Andriani (Siber Journal of Advanced Multidisciplinary, 2026)
Indonesia's traditional wet cake industry, such as glutinous rice cakes, layer cakes, and putu cakes, still use many synthetic dyes that are risky to health. Natural dyes are a safer alternative, because many are obtained from plants or food waste, such as pandan leaves, sugi leaves, and dragon fruit peels. The skin of the red dragon fruit (Hylocereus polyrhizus) has the potential to be an alternative to natural dyes because it contains high betacyanin which is antioxidant while providing an attractive purplish red color. This study aims to analyze the comparison of the sensory quality of pandan sticky rice talam cake (control) with glutinous rice talam cake with 50 ml of red dragon fruit peel extract. The research method used was a quantitative experiment with a comparative test approach (Independent Samples t-test), involving a rating test and a hedonic test conducted by 30 panelists, and analyzed by comparing the values of |tcalcul| against the table at a significance level of 5% (ttable = 2.00172). The results showed that the addition of dragon fruit peel extract had a significant effect on the quality of color (count 42.115 > table 2.00172) and aroma (count 8.494 > table 2.00172) organolepically, as well as on the level of color, texture, and taste preference (counts 5.220; 2.383; and 2.208 > table 2.00172), but did not have a significant effect on the organoleptic quality of shape, texture, and taste or the level of shape preference. The overall best treatment was sticky rice talam cake with dragon fruit peel extract (X1), although the panelists preferred the aroma of pandan sticky rice cake without extract (X0). This study proves that red dragon fruit peel extract can be used as a natural dye while improving the sensory quality of glutinous rice talam cake. Further research is recommended to examine the shelf life, antioxidant content, and nutritional value of the product.